Functionalization of carrageenan based edible film using Aloe vera for improved lipid oxidative and microbial stability of frozen dairy products. (October 2021) - Mahajan, Kanika; Kumar, Sunil; Bhat, Zuhaib F.; Naqvi, Zahra; Mungure, Tanyaradzwa E.; Bekhit, Ala El-Din A.
Abstract: The aim of the present study was to standardize, characterize and evaluate the efficacy of an A. vera -based edible film developed for improved microbial and lipid oxidative stability of frozen dairy products. Kulfi, a popular Indian ice cream, was used as a model system. The film was standardized using different levels of carrageenan (1.0, 1.5 and 2.0%), glycerol (12, 14 and 18%) and A. vera extract (9, 12 and 15%). Addition of A. vera increased the thickness (mm) and density (g/ml) whereas decreased the water vapor transmission rate (mg/m 2 t), transmittance (%) and lightness ( L* ) values of the film. A. vera extract increased the antioxidant capacity of the film and imparted antimicrobial properties against E. coli . The film containing optimum level of carrageenan (1.5%), glycerol (14%) and A. vera (15%) showed highest antioxidant and antimicrobial potential. Products packaged in AE (15%) film containing 15% A. vera extract showed significantly (p < 0.05) lower values for microbial counts (total plate, psychrophilic and yeast/mould, log10  cfu/g), free fatty acids (% oleic acid) and TBARS (mg malondialdehyde/kg) compared to control samples during six-month storage at −18 ± 1 °C. The developed film significantly improved the microbial and lipid oxidative stability of kulfi during storage and can be commercially used for improving storage stability of frozen dairy products. A. vera -based products can have a special health importance during pandemic of SARS-CoV-2 due to its strong immune boosting and antiviral properties.